1963
DOI: 10.1111/j.1476-5381.1963.tb01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Blocking Drugs on the Pressor Response to Physostigmine in the Rat

Abstract: Bretylium and guanethidine blocked the pressor effect of physostigmine and potentiated the responses to adrenaline and noradrenaline on the blood pressure of the rat. Morphine and atropine in small doses blocked the pressor effect of physostigmine without interfering with the actions of adrenaline and noradrenaline. Chlorpromazine in small doses (0.5 to 2.5 mg/kg) blocked the pressor effect of physostigmine and potentiated the responses to noradrenaline whilst those to adrenaline remained unaltered. 3,6-Di(3-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1964
1964
1983
1983

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Dirnhuber & Cullumbine (1955) and also Varagid (1955) showed that physostigmine increased blood pressure in the rat. Gokhale, Gulati & Joshi (1963) have found that this rise is completely blocked by bretylium and guanethidine, but only partially by hexamethonium even in very large doses. The effect of physostigmine is therefore exerted through the sympathetic nerves and perhaps in part at the sympathetic postganglionic terminations.…”
Section: Resultsmentioning
confidence: 94%
“…Dirnhuber & Cullumbine (1955) and also Varagid (1955) showed that physostigmine increased blood pressure in the rat. Gokhale, Gulati & Joshi (1963) have found that this rise is completely blocked by bretylium and guanethidine, but only partially by hexamethonium even in very large doses. The effect of physostigmine is therefore exerted through the sympathetic nerves and perhaps in part at the sympathetic postganglionic terminations.…”
Section: Resultsmentioning
confidence: 94%
“…McN-A-343 is a selective sympathetic ganglion stimulant in cats and dogs, and its pressor effects, which are attributed to increased peripheral adrenergic discharge, are blocked by bretylium (Roszkowski, 1961). The pressor action is unusual in that it is blocked by atropine but not by hexamethonium (Roszkowski, 1961 Cass & Spriggs, 1961;Varagic & Vojvodic, 1962;Gokhale et al, 1963;Spriggs, 1966). The pressor response to McN-A-343 is transient, well-defined and reproducible and is uncomplicated by the anticholinesterase disturbances associated with physostigmine.…”
Section: Effects On Noradrenalinementioning
confidence: 99%
“…Along with this the activating effect of vagal stimulation on heart phosphorylase a in the spinal rat suggested that there might be adrenergic fibers or mechanism in the cholinergic innervation within the heart. Gokhale et al (16) have shown that the pressor effect of physostigmine is reduced by antiadrenergic agents, hexamethonium, bretylium or guanethidine. There fore, it is possible to assume that the phosphorylase-activating action of physostigmine derives from noradrenaline or adrenaline endogenously liberated.…”
Section: Discussionmentioning
confidence: 99%